2013
DOI: 10.5817/cpr2013-2-16
|View full text |Cite
|
Sign up to set email alerts
|

Four aeroterrestrial algae grown at aspecial substrate of deglaciated coastal areas of Petuniabukta, Svalbard

Abstract: The bone remnants of sea mammals are frequently dispersed everywhere in coastal areas of Svalbard Archipelago represent aspecific natural habitat which is colonized by aeroterrestrial microscopic algae. Such bone habitat might be considered an analogue to stone substrates. However, bone habitats are not included in ecological studies of polar region. In the present study, thorough observations were made on some algal strains isolated to laboratory cultures. They included two green algal species Pseudodictyo-ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…3), the main gradient (Axis 1) is related to the level of eutrophication. On the right side of the diagram, there are fertile, ornithogenic sites (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(28)(29)(30), and 56-58 -wet turf, shallow puddles, streams, and ponds). This group of sites is predominated by nitrophilous species Prasiola crispa, Microcoleus autumnalis, and Phormidium irriguum (or Ph.…”
Section: Diversity Of Cyanobacteria and Green Algae In Different Typementioning
confidence: 99%
See 1 more Smart Citation
“…3), the main gradient (Axis 1) is related to the level of eutrophication. On the right side of the diagram, there are fertile, ornithogenic sites (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(28)(29)(30), and 56-58 -wet turf, shallow puddles, streams, and ponds). This group of sites is predominated by nitrophilous species Prasiola crispa, Microcoleus autumnalis, and Phormidium irriguum (or Ph.…”
Section: Diversity Of Cyanobacteria and Green Algae In Different Typementioning
confidence: 99%
“…Matuła [14,15], Oleksowicz and Luścińska [16], Oleksowicz et al [17], Skulberg [18], , Stibal et al [23], Matuła et al [24], Kim et al [25], Komárek et al. [26], Komárek and Kováčik [27], Pushkareva and Elster [28], and Raabová and Kováčik [29] provided similar information for the Svalbard archipelago in the European part of the Arctic. These data suggest that cyanobacteria and algae are important phototrophic components of biocenoses in almost all polar habitats.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, studies on the growth rate of lichens on alternative substrates are needed. The stable environment inside the bone is suitable for the growth of numerous organisms, including cyanobacteria and fungi (Raabová & Kovácik, 2013). These microenvironments may contribute to lichen and moss colonisation by acting as a trap for propagules and helping them to avoid abiotic stress; however, this assumption needs to be evaluated in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…The study on the cyanobacterial and algal flora of Svalbard is represented by a few principal works only (e.g. Oleksowicz et Luścinska 1992, Skulberg 1996, Leya et al 2000, Kaštovská et al 2005, Stibal et al 2006, Matuła et al 2007, Kim et al 2008, Richter et al 2009, Kim et al 2011, Kvíderová 2012, Raabová et Kováčik 2013. Arctic environments are considered to be relatively pristine and stable because of the absence of intensive local human activities.…”
Section: Introductionmentioning
confidence: 99%
“…In polar regions, the aero-terrestrial habitats like artificial substrates were poorly studied. The newly introduced man-made substrates are colonized by cyanobacteria and green algae, which principally grow in epiphytic and epilithic conditions (Karsten et al 2007, Raabová et Kováčik 2013. The study of these substrates showed an abundance of cyanobacteria and chlorophytes (Broady 1996, Olech 1996, Marshall et Chalmers 1997.…”
Section: Introductionmentioning
confidence: 99%